Axillary Artery Injury Accompanying Humeral Neck Fracture - Cawich, Shamir O.; Harnarayan, Patrick; Budhooram, Steve; Naraynsingh, Vijay (International Journal of Angiology, 2015)
Injuries to the axillary artery from proximal humeral fractures are uncommon. There are only 66 such injuries reported across the world literature to date. We report an additional case of axillary artery injury. This case highlights the importance of maintaining a high index of suspicion to prevent diagnostic delay.
Keywords: vascular; trauma; fracture; dislocation